MANHATTAN DISTANCE AND DICE SIMILARITY EVALUATION ON INDONESIAN ESSAY EXAMINATION SYSTEM - Ali, Muhammad Haidar; Rahutomo, Faisal (STKIP PGRI Tulungagung, 2019)
Each learning process requires an evaluation tool to measure the level of understanding of students. The type of evaluation can be multiple choice questions, short entries and essays. Some studies reveal essay exams better than other types of evaluations. An essay assessment is automatically needed to save teacher time in correcting answers. However, the development of essay assessments is still ongoing. The aim is to obtain a better accuracy value than the method used in the assessment. Based on these problems, this study proposes a comparative analysis of similarity methods for online essay exam assessment. The similarity method compared is Similarity Dice and Manhattan Distance. Both methods produce coefficient values which are then compared to the assessment of the system with manual scales with the same scale. The data used were 2162 data. This data was obtained from 50 students who answered 40 questions (politics, sports, lifestyle and technology). The data obtained in this study can be used to support other research that can be accessed at www.indonesian-ir.org. This research shows that the Dice similarity scheme is more accurate than Manhattan Distance